Festival Anak Sholeh sebagai Model Inovasi KKN: Kolaborasi Mahasiswa, Pemerintah Desa, dan Masyarakat dalam Meningkatkan Pendidikan Keagamaan - Dedi Masri; Fatimah Azzahra Putri; Ananda Utami; Sultan Khairul Fawaz; Muhammad Revandi Ananda (Al-Khidmah Jurnal Pengabdian Masyarakat, 2026)
The Festival Anak Sholeh (Righteous Children Festival) represents an innovative model of the Community Service Program (Kuliah Kerja Nyata / KKN) designed to strengthen religious education through a community-based approach. This activity was implemented in Manik Maraja Village, Dusun IV, Sidamanik District, Simalungun Regency, as a response to the community’s need for creative and educational spaces for children and adolescents. The festival featured a series of Islamic-themed competitions such as coloring, call to prayer (azan), short surah memorization, Islamic fashion show, and speech contests, culminating in an appreciation night with art performances and prize distribution. This study employed a descriptive qualitative approach, collecting data through participatory observation, interviews with village officials, religious leaders, KKN students, and documentation. Data were analyzed using Miles and Huberman’s interactive model, which includes data reduction, display, and conclusion drawing. The findings indicate that the Festival Anak Sholeh effectively enhanced children’s and adolescents’ religious literacy, strengthened community social cohesion, and fostered collaborative synergy among KKN students, village government, and the local community. Moreover, the festival served as an innovative model integrating educational, da’wah, and recreational functions rooted in Islamic values. The study concludes that a tripartite collaboration model in KKN implementation can significantly contribute to the sustainability of village-based religious programs. Its practical implication suggests that similar festivals can be replicated in other rural contexts with adequate government support and active community participation.